Deep Placement of Npk Briquette in Rice: Environment Friendly Technology for Sustainable Rice Production (Bangladesh Agronomy Journal, 2022)
Nine experiments were conducted at the Bangladesh Rice Research Institute (BRRI) farm, Gazipur, BRRI regional station, Sagardi, Barisal and farmers’ field of Barisal during Boro, T. Aus and T. Aman season, 2012 to evaluate the NPK briquette efficacy in rice production. Experimental results revealed that deep placement of NPK briquette (2 x 2.4 g) increased rice grain yield about 10 % and it saves 51, 9 and 20 kg NPK ha-1 than BRRI fertilizer recommended rate in Boro season. Similarly, NPK briquette (1 x 3.4 g) produced 28 and 18% more rice grain yield than BRRI fertilizer recommended rate with a savings of 29 kg N and 7 kg K ha-1 in T. Aus and T. Aman season, respectively. In general, deep placement method gave higher grain yield compared to conventional urea application. Undiscounted benefit cost ratio (BCR) was 1.44, 2.40 and 3.20 for Boro, T. Aus and T. Aman, respectively when comparing at the same rates of N application. Thus, use of NPK briquette over urea broadcast and incorporation was economically viable and efficient for rice cultivation. This method helps to reduce N loss through soil-water interface which plays a vital role in reducing environmental pollution.Bangladesh Agron. J. 2021, 24(2): 127-136